The Veil in Islamic Ethics: Revisiting the Muslim Authoritative Sources on Modesty - Belhaj, Abdessamad (Socio Religia, 2025)
This article discusses the headscarf in Muslim ethics, revisiting the Quran and hadith on modesty. By analyzing the veil in its discursive, social, and cultural manifestations, this article contributes to the historical sociology of Islamic norms and provides a diachronic understanding of Islamic modesty. We pay particular attention to how the laws of precaution and the intolerant minority contribute to the gradual establishment of a religious norm. We are particularly interested in how Islamic ethics evolved in response to the issues of changing societies and how a powerful and morally inflexible minority responds to these developments by pressuring the majority of society to become more conservative.